PENGAPLIKASIAN ACCELEROMETER SEBAGAI FEEDBACK PADA ARM ROBOT 5 DOF (DEGREE OF FREEDOM) - Sutisna, Setya Permana; Maulana, Erwin; Ahmad, Anton Royanto (UNIVERSITAS IBN KHALDUN BOGOR, 2019)
The automatic control system also able to implement using arm robot concept. In this research, 5 DOF (Degree of Freedom) arm robot control system using the close – loop control methode with the MPU 6050 Sensor which integrates the rotation of MG995 motor servo as feedback.Control of this robot using android – based aplication, the app send data of rotate angle for each servo motor which will rotate to a certain angle, afterward the data received by HC – 05 Bluetooth and the arduino UNO R3 process its data. Arduino UNO R3 microcontroller can control every rotation of each servo motor that integrated with an MPU6050 sensor with serial monitor communication to display the rotation of each servo motor. The test results obtained by the standard deviation value shows how large the sample diversity is. The result of this research show standard deviation correlation with the number of sample diversity. The higher standard deviation value will indicate more sample data spread (data diverse or varies), otherwise smaller standard deviation value will indicate homogenous sample data, and if standard deviation equals to zero it indicates sample has identical data. The highest standard deviation value from servo motor 1 is 5.20, servo motor 2 and 3 are 1.00, servo motor 4 is 2.89, and servo motor 5 is 2.9.